THE MEDIATING ROLE OF BRAND TRUST IN FACTORS INFLUENCING PURCHASE INTENTION SAFF & CO IN JAKARTA - Varensia; Galuh Mira Sakti (MANAJEMEN DEWANTARA, 2026)
SAFF & Co product sales growth percentage has decreased. Increasingly fieree competition forces SAFF & Co to devise appropriate strategies to prevent the emergence of new competitors. This aims to analyze the effects of eWOM, perceived quality and brand trust on purchase intention. The study empoloyed a quantitative research design using a descriptive method approach. The sample size in this study was 241 respondents using a purposive sampling method. Data were collected through as online survey and distributed via Google Form. The data analysis technique used SmartPLS 4 software. The research results show that eWOM, perceived quality and brand trust have a positive and significant effect on purchase intention. eWOM and perceived quality have a positive and significant effect on brand trust. Brand trust mediates the effect of eWOM and perceived quality on purchase intention. These results indicate that the three factors make a significant contribution to driving purchase intention therefore, companies need to optimize their makrketing strategies by focusing on the utilization of eWOM, perceived quality, and enhancing brand trust in order to reinforce their market position and competitiveness.